Malaysian traditional folklore for online trading card game using illustration: Bawang Putih Bawang Merah / Nur Insyirah Mohd Nasir - Mohd Nasir, Nur Insyirah (2019)
The newer generation’s recognition towards Malaysian folklore has slowly begun to fade away or dwindled from their minds as time passes due to the excess overexposure of westernized culture that that has fully dominated the international media, for example science fiction movies like Ironman. Malaysian folklore is one of the many treasures that was passed down to us to protect and preserve for the sake of our identity, culture and heritage. It is something that should be taken seriously and handled as most of the younger generation did not even know the local stories or characters such as “Badang”, “Puteri Santubong dan Puteri Sejenjang” and many more. In relation to this, it is decided that a study regarding Malaysian folklore using illustration design on an online trading card game, centering the popular folklore story “Bawang Putih and Bawang Merah “is to be made. The main purpose of this study is to ignite the new generation’s interest in Malaysian folklore as well as further educate and expose our culture using online trading card game as a platform due to its popular demand in the market and its easy acceptance of the public. There are several objectives towards this study, which is, to identify Malaysian Folklore and to create a new Malay folklore design style on online trading card games. This can give a new and different perspective on how Malaysian folklore culture can be spread in the near future. Furthermore, despite the lack of interest in it now, however by making it into the form of an online game it may not only spread awareness quickly, but it can also be made into an educational item. The cost of this outcome may be small, but it can give a huge impact towards the new generation’s sense of view in the importance of the Malaysian culture and heritage towards folklore.